Pengaruh Budaya Organisasi Dan Lingkungan Kerja Terhadap Stres Kerja Pegawai Pada Puskesmas 2x11 Kayutanam Kabupaten Padang Pariaman - Aize Selfa Sedayu; Sophan Sophian (GLOBAL SCIENTS PUBLISHER, 2026)
Work stress is one of the major issues that can affect employee performance and the quality of public health services. This study aims to examine the influence of organizational culture and the work environment on employees' work stress at the 2X11 Kayutanam Public Health Center, Padang Pariaman Regency. The study is based on theories of organizational culture, work environment, and work stress, which explain that organizational conditions and the work environment play important roles in shaping employees' behavior and psychological well-being. This research employed a quantitative approach with an associative research design. The population consisted of 34 employees, all of whom were selected as the research sample using the total sampling technique. Data were collected through observation, interviews, and questionnaires using a five-point Likert scale. Data analysis was conducted using validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test, F-test, and the coefficient of determination with the assistance of SPSS software. The findings indicate that organizational culture has a significant effect on employees' work stress, supporting the first hypothesis. Similarly, the work environment also has a significant effect on employees' work stress, supporting the second hypothesis. Therefore, organizational culture and the work environment are important factors influencing employees' work stress. Improving organizational culture and creating a supportive work environment are expected to reduce work stress and enhance the quality of healthcare services at the 2X11 Kayutanam Public Health Center, Padang Pariaman Regency.